Myeloid‐Lymphoid Ontogeny in the Rhesus Monkey (Macaca mulatta). Issue 8 (28th May 2014) - Batchelder, Cynthia A.; Duru, Nadire; Lee, Charles I.; Baker, Chris A.R.; Swainson, Louise; Mccune, Joseph M.; Tarantal, Alice F.
ABSTRACT Establishment of a functional immune system has important implications for health and disease, yet questions remain regarding the mechanism, location, and timing of development of myeloid and lymphoid cell compartments. The goal of this study was to characterize the ontogeny of the myeloid‐lymphoid system in rhesus monkeys to enhance current knowledge of the developmental sequence of B‐cell (CD20, CD79), T‐cell (CD3, CD4, CD8, FoxP3), dendritic cell (CD205), and macrophage (CD68) lineages in the fetus and infant. Immunohistochemical assessments addressed the temporal and spatial expression of select phenotypic markers in the developing liver, thymus, spleen, lymph nodes, gut‐associated lymphoid tissue (GALT), and bone marrow with antibodies known to cross‐react with rhesus cells. CD3 was the earliest lymphoid marker identified in the first trimester thymus and, to a lesser extent, in the spleen. T‐cell markers were also expressed midgestation on cells of the liver, spleen, thymus, and in Peyer's patches of the small and large intestine, and where CCR5 expression was noted. A myeloid marker, CD68, was found on hepatic cells near blood islands in the late first trimester. B‐cell markers were observed mid‐second trimester in the liver, spleen, thymus, lymph nodes, bone marrow spaces, and occasionally in GALT. By the late third trimester and postnatally, secondary follicles with germinal centers were present in the thymus, spleen, and lymph nodes. These results suggest that immune ontogeny in monkeys is similar in temporal and anatomical sequence when compared to humans, providing important insights for translational studies. Anat Rec, 297:1392–1406, 2014. © 2014 Wiley Periodicals, Inc.